2014
DOI: 10.15837/ijccc.2014.3.237
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Weighted Summation Type of Fuzzy Cluster Validity Indices

Abstract: Finding the optimal cluster number and validating the partition results of a data set are difficult tasks since clustering is an unsupervised learning process. Cluster validity index (CVI) is a kind of criterion function for evaluating the clustering results and determining the optimal number of clusters. In this paper, we present an extensive comparison of ten well-known CVIs for fuzzy clustering. Then we extend traditional single CVIs by introducing the weighted method and propose a weighted summation type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…Our findings are in line with previous studies that compared several CV indices on different simulated datasets and found that CV indices may fail to indicate the true number of clusters in noisy data that have high number of classes (Suleman 2017;Wang & Zhang 2007;Zhou et al 2014a). It might be the case their effectiveness might even be lesser given the complex nature of noise in MRI images with significant correlations between voxels (Gudbjartsson & Patz 1995;Parrish et al 2000).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings are in line with previous studies that compared several CV indices on different simulated datasets and found that CV indices may fail to indicate the true number of clusters in noisy data that have high number of classes (Suleman 2017;Wang & Zhang 2007;Zhou et al 2014a). It might be the case their effectiveness might even be lesser given the complex nature of noise in MRI images with significant correlations between voxels (Gudbjartsson & Patz 1995;Parrish et al 2000).…”
Section: Discussionsupporting
confidence: 92%
“…Previous work suggested that, when CV indices fail to agree on the true number of clusters for high-dimensional datasets, a combination of different indices into a single index should be considered (Sheng et al 2005;Zhou et al 2014a). Specifically, by using a weighted sum of several normalized CV indices, it has been shown that this weighted sum can improve the confidence of clustering solutions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To discovery valuable knowledge and fully realize the business potential of energy big data, various big data analytics techniques, such as data quality evaluation and modeling [103][104][105], data clustering and classification [68,[106][107][108][109], stream data processing [110][111][112], knowledge inference [113,114], statistical machine learning [115], neural networks modeling and deep learning [116,117], can be implemented on the data. The objective of energy big data analytics is to develop more effective and efficient data-driven applications and services.…”
Section: Energy Big Data Driven Applications In Energy Internetmentioning
confidence: 99%